Forms and directions of participation of educational organizations in the innovative activities of chemical enterprises - A. A. Efremov; A. S. Tutova; D. V. Vinokurov; S. V. Tutov (Путеводитель предпринимателя)
Successful innovation activity is one of the most important factors in the development of the national economy of the country. One of the main roles in achieving this goal is played by state stimulation of the process in the form of implemented programs and development strategies. The article analyzes the innovative maturity of the Russian Federation based on international and national indicators. The authors substantiate the importance of educational organizations in the formation of entrepreneurial and research competencies of future specialists, as well as their role in the innovative activity of the country. The subject of the study in the article is the forms and areas of participation of educational institutions in the innovative activity of the country using the example of chemical industry enterprises. The research results include the development of an interaction concept of educational institutions in innovative processes based on the integration of higher education institutions with secondary vocational education institutions into a single complex. The factors of successful implementation of the proposed mechanism are identified, which are aimed at increasing the interest of potential candidates in training in sought–after specialties, as well as further work at chemical industry enterprises. These factors include: the quality of the working environment and conditions in the region of residence of workers, as well as the automation of management processes in the company. The implementation of these factors was considered using the example of the activities of JSC OKH Uralchem in the field of implementing ESG strategy and digitalization of HR processes.